PENGARUH LABA KOTOR, LABA OPERASI DAN LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DIMASA MENDATANG PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI PERIODE 2013-2017 - zakia fadila (JURNAL ILMIAH KOHESI, 2018)
The company has its own capabilities in building and developing its business. Companies can be assessed through the ability to generate profits, maintain investment value and the company's ability to overcome corporate expenses that can be seen from financial performance. This study aims to determine the effect of the effect of gross profit, operating profit, and net income in predicting future cash flows in a Transportation Company Registered on the Stock Exchange for the 2013-2017 period. The analytical method used is multiple linear regression. The type of research used in this study is descriptive quantitative. The results of the study show that gross profit, operating profit, and net income are influential in predicting future cash flows in Transportation Companies Registered on the Stock Exchange for the 2013-2017 period. From the test results the coefficient of determination shows gross profit, operating profit, and net income to be able to explain the dependent variable that is cash flow of 25.5% while the remaining 74.5% is explained by other variables not used in this study